Perencanaan Sumber Daya Manusia Kesehatan Rumah Sakit Melalui Pelatihan Aplikasi Software Workload Indicators of Staffing Need: Hospital Health Human Resource Planning Through Software Application Training Workload Indicators of Staffing Need - Richa Noprianty; Winasari Dewi; Soni Muhsinin; Sri Soleha; Ina Sugiharti; Ivan Andriyansyah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Hospitals are one of the health services that are required to improve the quality of services that depend on the ability of human resources (HR). Therefore, planning HR needs must be calculated precisely based on needs. There are various approaches to calculating health workers, including the WISN method, where the calculation is based on workload. The purpose of this community service is to socialize the WISN software from WHO. This activity partnered with three hospitals, namely RSUD Subang with 16 people, RSUD Dr Slamet Garut with 18 participants, and RSUD Kota Bandung with 17 people. The activity is in progress from November to December 2023 and is carried out hybridly. The offline meeting was given a pre-test, then WISN socialization was carried out, and at the end, a post-test was given. Meanwhile, the online meeting invited speakers related to the WISN software application technicalities through the Zoom meeting application. Participants who attended were 51 people, consisting of hospital management. The pre-test results showed a mean value of 8.92 while the post-test value was 11.00, and the T-test results obtained a value of 0.02 (sig >0.05), meaning that there was an increase between the pre-test and post-test with an average increase of 2.29. The workshops and trainings went well. The hospital plans to calculate the workload using the WISN software as a comparison with the existing methods in the hospital.